The learning curve of V-NOTES hysterectomy: a single-surgeon experience - François Charles; Mathieu Luyckx; Nathanael Dubois (Frontiers in Medicine)
PurposeVaginal natural orifice transluminal endoscopic surgery (V-NOTES) has emerged as an innovative surgical approach that combines the advantages of endoscopic surgery with those of the vaginal approach. This article presents the initial experience of a single institution in implementing the V-NOTES technique for hysterectomy procedures.MethodsThis retrospective cohort study assessed the first 139 V-NOTES hysterectomies performed by a single surgeon at 000 from 2021 to 2024. Preoperative, intraoperative, and postoperative data were recorded. Operative time (OT) served as an indicator of surgical proficiency. The learning curve was analyzed using the cumulative sum method of operative time (CUSUMot).ResultsThe mean OT was 59.32 ± 21.13 min. No patient required conversion to laparotomy or conventional laparoscopy. The CUSUMot analysis demonstrated four phases in the learning curve: initiation (12 patients; mean OT, 66.17 ± 12.84 min), consolidation (41 patients; mean OT, 54.32 ± 13.96 min), complexification (54 patients; mean OT, 64.46 ± 25.48 min), and mastery (32 patients; mean OT, 54.5 ± 21.11 min). Additionally, the study identified a history of cesarean section and the absence of vaginal delivery as two risk factors for bladder injury.ConclusionThis study identifies a four-phase learning curve for V-NOTES hysterectomy, with initial competency achieved after 12 cases and sufficient mastery reached after 53 cases for an experienced surgeon.